Our work is everywhere : an illustrated oral history of queer & trans resistance - Rose, Syan, 1990- (Arsenal Pulp Press, 2021)
"A visually stunning graphic non-fiction book on queer and trans resistance. Over the past ten years, we have witnessed the rise of queer and trans communities that have defied and challenged those who have historically opposed them. Through bold, symbolic imagery and surrealist, overlapping landscapes, queer illustrator and curator Syan Rose shines a light on the faces and voices of these diverse, amorphous, messy, real, and imagined queer and trans communities. In their own words, queer and trans organizers, artists, healers, comrades, and leaders speak honestly and authentically about their own experiences with power, love, pain, and magic to create a textured and nuanced portrait of queer and trans realities in America. The many themes include Black femme mental health, Pacific Islander authorship, fat queer performance art, disability and health care practice, sex worker activism, and much more. Accompanying the narratives are Rose's startling and sinuous images that brings these leaders' words to visual life. Our Work Is Everywhere is a graphic non-fiction book that underscores the brilliance and passion of queer and trans resistance. Includes a foreword by Lambda Literary Award-winning author and activist Leah Lakshmi Piepzna-Samarasinha, author of Care Work: Dreaming Disability Justice."--